Veterinary ethics and companion animal euthanasia: what can we learn from critical disability studies? - Arathoon, Jamie; Van Patter, Lauren (Frontiers in Veterinary Science, 2024)
Within veterinary ethics and practice around companion animal end-of-life and euthanasia, the political and cultural dimensions of death and dying are rarely addressed. This reduces the ability to engage with questions like: what future potential goods (positive affective states, meaning) could an animal experience by continuing to live; what constitutes a life worth living; and how can we make this decision for another being? These are questions that have been subject to extensive dialogue within Critical Disability Studies. The aim of this paper is to provide an analysis of how core considerations from Critical Disability Studies could be useful in veterinary ethics when considering companion animal end of life and euthanasia. First, critiques of the dis/ability binary and associated hierarchies raise questions about how animal disability and illness are understood, and around challenging questions like psychological illness and behavioural euthanasia. Second, nuanced engagements with questions of a life worth living and Quality of Life emphasise the importance of individual animal experiences, personality, and the foregrounding of ‘what is important for the animal’. Third, dialogues around choice and agency critique the tendency to focus on owner choice, rather asking what opportunities there are to listen to the preferences of animals themselves. Finally, engaging with care and power highlights the ambivalent nature of caregiving, of euthanasia as a practice of care, and the power intrinsic to making End of Life decisions on behalf of another. Overall, perspectives from Critical Disability Studies allow us to engage with challenging questions of veterinary ethics and end-of-life care in companion animal practice with more nuance and complexity.